2002
DOI: 10.1248/cpb.50.1514
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Terpenoids from Laurus nobilis L.

Abstract: Trypanosoma cruzi, a parasitic protozoan of Zoomastigophoria, is the etiologic agent of Chagas' disease which is endemic in Central and South America.1) In our screening work on medicinal plants used in Asian counties for trypanocidal activity, extracts of the dried leaves of Laurus nobilis L. (Lauraceae) showed strong trypanocidal activity against epimastigotes of T. cruzi. Leaves of L. nobilis are used as a spice known as laurel or bay leaf. They are also used as a folk medicine for rheumatism and scabies.2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 19 publications
3
28
0
2
Order By: Relevance
“…The minimum lethal concentrations of these compounds against epimastigotes of T. cruzi were 7 lM and 25 lM, respectively (Asaruddin et al, 2003). Also dehydrocostus lactone (142) and zaluzanin D (148) showed lethal activity against epimastigotes of T. cruzi at concentrations of 6.3 and 2.5 lM, respectively (Uchiyama et al, 2002).…”
Section: Antiprotozoalmentioning
confidence: 99%
“…The minimum lethal concentrations of these compounds against epimastigotes of T. cruzi were 7 lM and 25 lM, respectively (Asaruddin et al, 2003). Also dehydrocostus lactone (142) and zaluzanin D (148) showed lethal activity against epimastigotes of T. cruzi at concentrations of 6.3 and 2.5 lM, respectively (Uchiyama et al, 2002).…”
Section: Antiprotozoalmentioning
confidence: 99%
“…Several sesquiterpene lactones have been reported to show trypanocidal activity. Results suggest the mechanism of action of this group of compounds relies on covalent bond formation of the a,b-unsaturated c-lactone moiety with nucleophiles that are essential for the life of the parasite (Uchiyama et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…33 Our studies demonstrate that K. senegalensis bark also possesses anti-Giardial activity. Whilst, further studies are required to identify the active component(s), previous studies have identified several similar terpenoids in plants 49 and marine sponges 50 which inhibit the growth of parasitic protozoans. The former of these studies is of particular note as it correlates trypanocidal activity with similar sesquiterpenoid lactones as those detected in our study.…”
Section: Discussionmentioning
confidence: 99%